Possible role of hemichannels in cancer - Schalper, Kurt A.; Carvajal-Hausdorf, Daniel; Oyarzo, Mauricio P. (Frontiers in Physiology, 2014)
In humans, connexins (Cxs) and pannexins (Panxs) are the building blocks of hemichannels. These proteins are frequently altered in neoplastic cells and have traditionally been considered as tumor suppressors. Alteration of Cxs and Panxs in cancer cells can be due to genetic, epigenetic and post-transcriptional/post-translational events. Activated hemichannels mediate the diffusional membrane transport of ions and small signaling molecules. In the last decade hemichannels have been shown to participate in diverse cell processes including the modulation of cell proliferation and survival. However, their possible role in tumor growth and expansion remains largely unexplored. Herein, we hypothesize about the possible role of hemichannels in carcinogenesis and tumor progression. To support this theory, we summarize the evidence regarding the involvement of hemichannels in cell proliferation and migration, as well as their possible role in the anti-tumor immune responses. In addition, we discuss the evidence linking hemichannels with cancer in diverse models and comment on the current technical limitations for their study.